2018
DOI: 10.6001/biologija.v64i3.3825
|View full text |Cite
|
Sign up to set email alerts
|

The golden jackal Canis aureus – a new species in the Baltic countries

Abstract: In the Baltic countries, the golden jackal (Canis aureus) was first recorded in Estonia on 28 February 2013 and three specimens of golden jackal were hunted in Latvia in 2014. The first golden jackal in Lithuania was hunted on 7 February 2015. The species of the golden jackal was identified using morphological and mitochondrial DNA control region (CR1) analysis. In Lithuania, hunting of these animals is permitted throughout the year. Few studies in the past revealed the potential role of the golden jackal as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The seasonal synchronization of nymphal and larval feeding patterns was found in Ixodes scapularis populations in the Midwestern United States. Investigations into the infection pattern of Borrelia burgdorferi sensu lato indicated that lineages carrying 16S-23S rRNA intergenic spacer restriction fragment lead to lengthen the polymorphism sequence of type 1 which is more commonly identified in Northeastern Ixodes populations (Paulauskas 2023).…”
Section: Tick Physiologymentioning
confidence: 99%
“…The seasonal synchronization of nymphal and larval feeding patterns was found in Ixodes scapularis populations in the Midwestern United States. Investigations into the infection pattern of Borrelia burgdorferi sensu lato indicated that lineages carrying 16S-23S rRNA intergenic spacer restriction fragment lead to lengthen the polymorphism sequence of type 1 which is more commonly identified in Northeastern Ixodes populations (Paulauskas 2023).…”
Section: Tick Physiologymentioning
confidence: 99%
“…Germany, Poland, Denmark, the Baltic States, Finland, the Netherlands, France) (e.g. Möckel, 2000;Weingarth et al, 2012;Banea et al, 2013;Kowalczyk et al, 2015Kowalczyk et al, , 2020Maran, 2015;Rutkowski et al, 2015;Stratford, 2015;Pyšková et al, 2016;Paulauskas et al, 2018). This expansion made the golden jackal one of the most abundant carnivore species with a population size estimated to be between 97,000 and 117,000 individuals in Europe (Ranc et al, 2019).…”
Section: Golden Jackal In Europementioning
confidence: 99%
“…The golden jackal has been recorded as far as in northern Norway (Sørensen & Lindsø 2021). The species was for the first time recorded in Estonia in 2011, in Latvia in 2013 and in Lithuania in 2015 (Paulauskas et al 2018). The migrating individuals have already reached western Europe and the species appeared in Denmark in 2015 (Tillmann 2020), the first record doi: 10.37520/lynx.2023.012 in the Netherlands was made in 2016 (van der Grift 2016).…”
Section: Introductionmentioning
confidence: 99%